2015
DOI: 10.1097/xeb.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Conducting systematic reviews of economic evaluations

Abstract: The updated JBI guidance will be useful for researchers wanting to synthesize evidence about economic questions, either as stand-alone reviews or part of comprehensive or mixed method evidence reviews. Although the updated methodology produced by the work of the working group has improved the JBI guidance for systematic reviews of economic evaluations, there are areas where further work is required. These include adjusting the critical appraisal tool to separate out questions addressing intervention cost and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 4 publications
0
104
0
5
Order By: Relevance
“…For example, they recommend some key features to be critically appraised (including model type, perspective, costs included and others) and they developed a set of guidelines for improving SREE [32], suggesting that ICERs for each comparison should be reported along with the input parameters to better understand the results. Different methods have been suggested on how to present the result in a simplified manner such as the three-by-three dominance ranking matrix (DRM) tool [14,33], harvest plot [34] and hierarchical method [16,35]. Others have discussed the use of the QA tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they recommend some key features to be critically appraised (including model type, perspective, costs included and others) and they developed a set of guidelines for improving SREE [32], suggesting that ICERs for each comparison should be reported along with the input parameters to better understand the results. Different methods have been suggested on how to present the result in a simplified manner such as the three-by-three dominance ranking matrix (DRM) tool [14,33], harvest plot [34] and hierarchical method [16,35]. Others have discussed the use of the QA tools.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al [36] highlighted the complexity and impracticality of checklists and suggested a 5-dimension framework on good practice procedure in modelling. Gomersall et al [33] suggested separating multi-component questions into single items to avoid ambiguity.…”
Section: Discussionmentioning
confidence: 99%
“…A study was considered to have studied safety if any outcome studied satisfied the definition of harms as in PRISMA-Harms guidelines for SRMAs (encompassing various terms such as “adverse drug reaction,” “adverse effect,” “adverse event,” “complication,” “harm,” “safety,” “side effect,” and “toxicity”) [38]. Studies were deemed having other outcomes as per their established definitions in context of SRMAs (eg, diagnostic [39], prognostic [40], epidemiological (etiological/descriptive/association) [4143], economic analysis [44]). A single SRMA could have multiple types of outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…This review was conducted in accordance with the Joanna Briggs Institute (JBI) guidance for the systematic review of economic evaluation evidence [30]. A protocol for this systematic review was registered with the PROSPERO International Prospective Register of Systematic Reviews on 30 January 2015 (http://www.crd.york.ac.uk/PROSPERO; registration number CRD42015015977).…”
Section: Methodsmentioning
confidence: 99%